Bilateral strength testing in dominant and non-dominant plant leg in soccer players - Warren, B. L.; Abellanida, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to examine bilateral dynamic strength differences of the knee flexors and extensors in both the dominant and non-dominant plant legs (PL) in NCAA Division III collegiate players. Sixteen male and female soccer players participated in the study. The strength of the knee flexors and extensors of both dominant and non-dominant PL was measured using a CYBEX NORM isokinetic dynamometer at 60, 120, and 180 deg/sec with a 1-minute rest between each velocity set. Dependent t-test (alpha<0.05) results suggest there was no significant strength difference between dominant and non-dominant PL. Therefore it was concluded that these Division III soccer players did not exhibit significant bilateral strength differences as was found in other studies.